Polysemy Found in Sir Alex Ferguson Interview on Beanyman Sport - Muhammad Azmi Bahari; Ervina CM Simatupang (Universitas Cokroaminoto Palopo, 2022)
Polysemy is a type of lexical relation which refers to a word that has more than one meaning. The word polysemy comes from the Greek word poly- which means